2018
DOI: 10.3390/nu10020173
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Japanese Traditional Diet in Healthy and Sustainable Dietary Patterns around the World

Abstract: As incomes steadily increase globally, traditional diets have been displaced by diets that are usually animal-based with a high content of “empty calories” or refined sugars, refined fats, and alcohol. Dietary transition coupled with the expansion of urbanization and lower physical activity have been linked to the global growth in the prevalence of obesity, overweight and life style-related non-communicable diseases. The challenge is in how to reverse the trend of high consumption of less healthy food by more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(49 citation statements)
references
References 97 publications
3
45
0
1
Order By: Relevance
“…It is important to also highlight that the included studies were from Japan and the US, two countries with very different cultural contexts and eating habits [46,47]. Landmark studies such as the NiHonSan study, which compared cardiovascular risk in Japanese men living in Japan, Hawaii, and California following post-World War II migration, illustrated the importance of environmental and dietary behavioral factors as contributors to cardiovascular risk, and found that living in a ‘Western’ environment was associated with increased CV risk [48].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to also highlight that the included studies were from Japan and the US, two countries with very different cultural contexts and eating habits [46,47]. Landmark studies such as the NiHonSan study, which compared cardiovascular risk in Japanese men living in Japan, Hawaii, and California following post-World War II migration, illustrated the importance of environmental and dietary behavioral factors as contributors to cardiovascular risk, and found that living in a ‘Western’ environment was associated with increased CV risk [48].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the Korean diet, the traditional Japanese diet (known as Washoku) is characterized by small portions of multiple components, primarily including rice, fish (often eaten raw), soups, and pickles [95]. Fermented soybean paste (dashi) serves as the base of many of the soups that are central to the traditional Japanese diet; other ingredients include seaweed, fruits and vegetables, and mushrooms.…”
Section: Traditional Asian Dietsmentioning
confidence: 99%
“…29 30 Therefore, the traditional meal culture and nutritional components of meals in the country may not pose problems. 7 Nevertheless, the assessment of dietary patterns is beyond the scope of our study and these could not be interpreted directly from the results of our study. Similarly, elderly people often have problems such as social isolation, economic problems 31 and impaired oral status 32 that could decrease their ability to eat.…”
Section: Discussionmentioning
confidence: 85%
“…5 Like in other developed nations, lifestyle-related diseases are also prevalent in Japan, and the Japanese government has implemented a national health promotion programme to address the issues associated with various non-communicable diseases. 6 Although traditional Japanese food and eating styles are healthy, owing to large variety, small portion sizes, inclusion of soups, high vegetable intake and high water content, 7 Westernisation has led to an increase in the proportion of people with unhealthy dietary habits. 8 9 As a result, there is a steady increase in people's calorie intakes, as well as the popularity of fast foods and beverages.…”
Section: Introductionmentioning
confidence: 99%